The Twin Effects of Globalization - Francesco Daveri; Paolo Manasse; Danila Serra (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2003)
Employees of .globalized. firms face a riskier, but potentially more rewarding, menu of labor market outcomes. We document this neglected trade-off of globalization for a sample of Indian manufacturing firms. On the one hand, the employees of firms subject to foreign competition face a more uncertain stream of earnings and riskier employment prospects. On the other, they enjoy a more rapid career and/or have more opportunities to train and upgrade their skills. The negative uncertainty costs and the positive incentive effects of globalization are thus twin to each other. Concentrating on just one side of the coin gives a misleading picture of globalization.
Keywords: 330